Fiber-based coherent polarization beam combining with cascaded phase-locking and polarization-transforming controls. (18th April 2018) - Yang, Yan; Geng, Chao; Li, Feng; Huang, Guan; Li, Xinyang
Abstract: In this paper, the fiber-based coherent polarization beam combining (CPBC) with cascaded phase-locking (PL) and polarization-transforming (PT) controls was proposed to combine imbalanced input beams where the number of the input beams is not binary, in which the PL control was performed using the piezoelectric-ring fiber-optic phase compensator, and the PT control was realized by the dynamic polarization controller, simultaneously. The principle of the proposed CPBC was introduced. The performance of the proposed CPBC was analyzed in comparison with the CPBC based on PL control and the CPBC based on PT control. The basic experiment of CPBC of three laser beams was carried out to validate the feasibility of the proposed CPBC, where cascaded controls of PL and PT were implemented based on stochastic parallel gradient descent algorithm. Simulation and experimental results show that the proposed CPBC incorporates the advantages of the two previous CPBC schemes and performs well in the closed loop. Moreover, the expansibility and the application of the proposed CPBC were validated by scaling the CPBC to combine seven laser beams. We believe that the proposed fiber-based CPBC with cascaded PL and PT controls has great potential in free space optical communications employing the multi-aperture receiver with asymmetric structure.